CSC128 - Fundementals of Computer Problem Solving / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2018)
This course is an introduction to problem solving using computers. It emphasizes various aspects of problem solving, mainly consisting of the problem domain, phases of problem solving and basic techniques in designing a solution. The approach to problem solving is via top-down design, structured and modular programming. The emphasis is on solving problems using computer rather than the syntactical aspects of the chosen programming language.